2019
DOI: 10.1039/c9ra01481k
|View full text |Cite
|
Sign up to set email alerts
|

An efficient 3-acylquinoline synthesis from acetophenones and anthranilviaC(sp3)–H bond activation mediated by Selectfluor

Abstract: An efficient method for the synthesis of 3-functionalized quinolines from acetophenones and anthranil mediated by Selectfluor was achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…From this experiment, it can be concluded that the aryl sodium sulfinate ( 2a ) is more nucleophilic than benzotriazole ( 2ab ). Based on these mechanistic insights and previous literature, a plausible reaction mechanism is proposed (Figure B). Dimethyl sulfoxide (DMSO) is activated by Selectfluor to produce a methyl­(methylene)­sulfonium cation, which then reacts with imidazopyridine ( 1a ) to form a key intermediate 2aa , followed by nucleophilic displacement of SCH 3 with 2a or 2ab results in the formation of 3a or 4a .…”
Section: Resultsmentioning
confidence: 60%
“…From this experiment, it can be concluded that the aryl sodium sulfinate ( 2a ) is more nucleophilic than benzotriazole ( 2ab ). Based on these mechanistic insights and previous literature, a plausible reaction mechanism is proposed (Figure B). Dimethyl sulfoxide (DMSO) is activated by Selectfluor to produce a methyl­(methylene)­sulfonium cation, which then reacts with imidazopyridine ( 1a ) to form a key intermediate 2aa , followed by nucleophilic displacement of SCH 3 with 2a or 2ab results in the formation of 3a or 4a .…”
Section: Resultsmentioning
confidence: 60%
“…Finally, a spontaneous demethylthioation or demethylsulfinylation yields the intermediate 12E and MeSH or MeS(O)H (Scheme 13). 32…”
Section: C–s Bond Cleavage In Sulfoxidesmentioning
confidence: 99%
“…[28] Very recently, the same group reported a novel and efficent strategy for the construction of 3-acylquinoline by using acetophenone, anthranil and DMSO as the strating materials through a Selectuor mediated three-component reaction (Scheme 14c). [29] It was noteworthy to mention that DMSO served as both a carbon and solvent source.…”
Section: The Application Of Selectfluor As a Fluorine Cation Initiator 31 Selectfluor As A Fluorinated Intermediate Initiatormentioning
confidence: 99%